Disease Conditions in Farm and Smallholder Buffaloes of Serdang, Malaysia - Saad, Mohd Zamri; Saharee, Abdul Aziz; Abdullah, M. N. (1988)
Analysis of records revealed that there were no significant differences in the number of disease Conditions between buffaloes of the smallholders and Universiti Pertanian Malaysia (UPM) farm, and between the calves and adult buffaloes of both groups. Significant differences were, however, observed on the type of disease conditions involved. The differences were probably associated with the system of management.